Pemetaan Ilmiah Topik Penelitian Perluasan Layanan Bus Rapid Transit (BRT) Trans Jateng - Nugraheni, D.W.; Rochim, A.; Karlinasari, R. (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2024)
Bus Rapid Transit (BRT) is one of the types of bus-based public transportation that provides fast, convenient, and affordable urban transportation. The BRT service in Central Java is called Trans Jateng and is managed by the Transportation Agency of Central Java Province. The operational concept of Trans Jateng is to serve routes that connect urban agglomeration areas in the province of Central Java. Trans Jateng plans to develop future services grouped into service corridors based on the existing development areas in Central Java, including the Kedungsepur, Wanarakuti, Banglor, Bregasmalang, Petanglong, Subosukowonosraten, Barlingmascakeb, and Purwomanggung agglomerations. In addition to opening new corridors, the development of Trans Jateng BRT services can also be carried out by expanding existing services; therefore, a comprehensive study is essential to monitor and track the progress of the research. This paper will map the literature on service expansion, BRT, and Trans Jateng. The literature database was taken from Google Scholar and analyzed using the VOSviewer tool with a mapping of previous research. The results of this research are highly useful for understanding the current development of research on the expansion of Trans Jateng BRT services in the future.